SISTEM INFORMASI ABSENSI KARYAWAN UNTUK PERHITUNGAN GAJI PADA CV. SUMBER LUMAS SEMARANG - vivi kumalasari subroto (UNIVERSITAS STEKOM, 2020)
Abstract The employee attendance is proof of the presence of an employee in the office or where he works. It is one of the factors assessing the discipline of an employee, whether the employee often arrives late, permits, or does not enter work. On CV. Sumber Lumas Semarang, the owner will cut the salary out for employees who arrive late or those who do not work for specific reason. Because of that, there are employees who do unfair to their manual attendance to avoid salary deductions. Another reason is the human error, calculation error, which was conducted by the owners. There are many ways that can be done by the owner to collect data. One of them is using fingerprint attendance machines. By using it, an employee cannot do the attendances unfair and the owner will also calculate employee salaries easily. It is because the fingerprint machine is able to detect employee data and their attendance hours through fingerprints of each employee. Attendance information system using fingerprint machine will be applied to solve the problems. By using this system, it is expected to avoid fraud in employee attendance and help the owner to calculate the salaries accurately